Do School Lunch Subsidies Change the Dietary Patterns of Children from Low- Income Households? - Larry Howard; Nishith Prakash (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2011)
This article examines the effects of school lunch subsidies provided through the meanstested component of the National School Lunch Program on the dietary patterns of children age 10- to 13 yr in the USA. Analyzing data on 5,140 public school children in 5th grade during spring 2004, we find significant increases in the number of servings of fruit, green salad, carrots, other vegetables, and 100 percent fruit juice consumed in one week for subsidized children relative to unsubsidized children. The effects on fruit and other vegetable consumption are stronger among the children receiving a full subsidy, as opposed to only a partial subsidy, and indicate the size of the subsidy is an important policy lever underlying the program's effectiveness. Overall, the findings provide the strongest empirical evidence to date that the means-tested school lunch subsidies increase children's consumption over a time period longer than one school day.
Keywords: H51; I12; I38; 330; National School Lunch Program; Dietary Patterns; Means-Tested Subsidies